2019
DOI: 10.17796/1053-4625-43.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Factors Related to Caries in Children with Autism

Abstract: Many predisposing factors to caries are present in autism, however, it is unlikely that autistic patients exhibit higher caries indexes than the rest of the population. Objective: To evaluate salivary factors related to caries in autistic patients. Study design: 34 autistics and 34 controls aged between 4–13 years old were included. Decayed, missing, and filled teeth (DMFT) index and oral hygiene simplified index (IHO-S) were assessed, as well as, pH, total proteins, phosphate, calcium and IgA in saliva. All d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…Studies in the literature indicate that the secretion of these components in unstimulated saliva is influenced by the size of the salivary glands, which would result in a difference between sexes, since these glands are smaller in women 24 . In the unstimulated saliva of ASD carriers, a higher concentration of proteins was described 25 , however, the authors did not perform a subdivision of donors according to sex. In this pilot study, the number of participants was reduced, 12 in each group, and it was not possible to consider the reproductive maturity of the girls, which we consider a limitation of the study and which may justify the fact that we did not observe a difference in the concentration of proteins between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature indicate that the secretion of these components in unstimulated saliva is influenced by the size of the salivary glands, which would result in a difference between sexes, since these glands are smaller in women 24 . In the unstimulated saliva of ASD carriers, a higher concentration of proteins was described 25 , however, the authors did not perform a subdivision of donors according to sex. In this pilot study, the number of participants was reduced, 12 in each group, and it was not possible to consider the reproductive maturity of the girls, which we consider a limitation of the study and which may justify the fact that we did not observe a difference in the concentration of proteins between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…However, some other studies reported different observations and stated that the means of decayed, missed, filled, and permanent teeth in the primary dentition are lower in children with ASD compared with healthy controls [ 49 ]. Surprisingly, a lower incidence of caries was observed in ASD patients compared to healthy controls [ 46 , 50 ]. However, this finding might be caused by more intensive assistance provided by their parents or caregivers that varies from case to case [ 46 , 47 ].…”
Section: Saliva In Asd Researchmentioning
confidence: 99%
“…Otra posible explicación es el consumo de fármacos para el tratamiento de ciertos síntomas, causando hiposialia y aumentando el riesgo cariogénico 11 . Contrariamente, otros estudios proponen una menor prevalencia de caries que la población general producto de ciertos factores protectores en la saliva de pacientes con TEA 12 . Sin embargo, los últimos estudios indican que no existen resultados concluyentes, por lo que es necesaria más investigación 13 .…”
Section: Presentación Clíncaunclassified